2021
DOI: 10.2147/ndt.s298050
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Long-Acting Injectable Antipsychotics in Outpatient Care: A Retrospective Analysis

Abstract: Purpose Antipsychotic efficacy in schizophrenia depends on its availability in the body. Although therapeutic outcomes remain still far from satisfactory, therapeutic drug monitoring is not a common part of clinical practice during treatment with long-acting injectable antipsychotics (LAI AP). The real effectiveness of LAI AP is thus uncertain. Patients and Methods We made a retrospective evaluation of plasma levels of LAI AP. Collection of blood samples was performed j… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“… 17 , 19 , 35 , 39 , 55 In short, knowing the relationship between dose and PLs, and between PLs and effectiveness and tolerability, would enable optimization of treatment. 41 , 43 , 45 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 17 , 19 , 35 , 39 , 55 In short, knowing the relationship between dose and PLs, and between PLs and effectiveness and tolerability, would enable optimization of treatment. 41 , 43 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic monitoring could help to overcome this uncertainty. 27 , 45 , 57 , 58 It has to be noted that the vast majority of patients have been previously treated with other antipsychotics without acceptable results, and a considerable number would be candidates for clozapine because they are “resistant”. 49 , 50 (In fact, some of them combine clozapine with AOM or PP3M).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of lower-than-expected LAI serum levels proved to be remarkably common and in-line with previous realworld data on psychotropic drugs, 42 including LAIs. 21,23,43 More specifically, O-LAI proved to be most commonly associated with underrange values, which may be explained by various factors, including the fact that olanzapine metabolism is strongly influenced by cytochrome inducers such as cigarette smoke. 44,45 This is widely represented among individuals with psychotic disorders and may therefore increase the likelihood of subtherapeutic doses when choosing a monthly administration.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of 13,217 outpatients with psychotic disorders (Smith et al, 2021) suggested a complete nonadherence rate (undetectable blood level) of ~5% as a whole and a nonadherence rate of 2.4% in risperidone-treated patients. Another retrospective analysis of 40 outpatients treated with long-acting injectable antipsychotics (Hýža et al, 2021) also suggested a high incidence of plasma levels of drugs below their therapeutic reference ranges. Differed from inpatients, the medication compliance, blood testing time, and living habits of outpatients may all affect the plasma levels of antipsychotics.…”
Section: Introductionmentioning
confidence: 99%